A “Catalyst Switch” Strategy for the Sequential Metal-Free Polymerization of Epoxides and Cyclic Esters/Carbonate - Zhao, Junpeng; Pahovnik, David; Gnanou, Yves; Hadjichristidis, Nikos (Macromolecules, 2014)
A “catalyst switch” strategy was used to synthesize well-defined polyether–polyester/polycarbonate block copolymers. Epoxides (ethylene oxide and/or 1,2-butylene oxide) were first polymerized from a monoalcohol in the presence of a strong phosphazene base promoter (t-BuP4). Then an excess of diphenyl phosphate (DPP) was introduced, followed by the addition and polymerization of a cyclic ester (ε-caprolactone or δ-valerolactone) or a cyclic carbonate (trimethylene carbonate), where DPP acted as both the neutralizer of phosphazenium alkoxide (polyether chain end) and the activator of cyclic ester/carbonate. This work has provided a one-pot sequential polymerization method for the metal-free synthesis of block copolymers from monomers which are suited for different types of organic catalysts.